Validity and reliability of Turkish version of St. George's respiratory questionnaire - Polatli, Mehmet; Yorgancioglu, Arzu; Aydemir, Omer; Demirci, Nilgun Yilmaz; Kirkil, Gamze; Nayci, Sibel Atis; Gunakan, Gonca (Turkish Assoc Tuberculosis & Thorax, 2013)
Introduction: The importance of the evaluation of health status in chronic obstructive pulmonary disease (COPD) is recently highlighted in many studies. In this study, we aimed to test the validity and reliability of the Turkish version of St. George Respiratory Questionnaire (SGRQ). Materials and Methods: The study was conducted in seven centers in Turkey. Three hundred and twenty one COPD patients (40-75 years) were included to the study. Turkish versions of breathlessness, Cough, and Sputum Scale (BCSS), mMRC (Modified Medical Research Council) dyspnea scale, SGRQ, COPD assessment test (CAT) and Short Form Health Survey (SF-36) were carried out to the patients. The statistical analysis of SGRQ was performed by using the coefficient of internal consistency, discriminative analysis for different stages and the correlation with the other scales. Results: The mean age was 62.4 +/- 8.9 years and the mean FEV1 was 51.9 +/- 19.2% pred. The coefficient of internal consistency (Cronbach alpha) was 0.8815. The correlation between the total score measured initially and that obtained two weeks later was found to be highly significant (r= 0.90, p< 0.0001). According the results of validation of both total score and the components of SGRQ, the correlation between the total score of SGRQ and CAT was 0.782 (p< 0.0001), SGRQ and SF36 was between -0.481 ile -0.819 (p< 0.0001). The total and component scores were able to discriminate different disease stages and a significant correlation was found to be with pulmonary function tests. Conclusion: SGRQ Turkish version is a reliable and valid assessment tool for COPD patients in clinical practice.
St. George solunum anketinin Türkçe geçerlilik ve güvenilirli?i
Keywords: COPD; St. George Respiratory Questionnaire (SGRQ); validity and reliability